A Burkholderia pseudomallei type III secreted protein, BopE, facilitates bacterial invasion of epithelial cells and exhibits guanine nucleotide exchange factor activity. - Stevens, M; Friebel, A; Taylor, L; Wood, M; Brown, P; Hardt, W; Galyov, E (2003)
We report the characterization of BopE, a type III secreted protein that is encoded adjacent to the Burkholderia pseudomallei bsa locus and is homologous to Salmonella enterica SopE/SopE2. Inactivation of bopE impaired bacterial entry into HeLa cells, indicating that BopE facilitates invasion. Consistent with this notion, BopE expressed in eukaryotic cells induced rearrangements in the subcortical actin cytoskeleton, and purified BopE exhibited guanine nucleotide exchange factor activity for Cdc42 and Rac1 in vitro.